Determinazione di pesticidi organoclorurati in sedimenti di laghi artici e antartici - TULLO, ALESSANDRO (Pisa University, 2024)
This study presents an optimized analytical method for the detection of trace and ultra-trace organo-pesticides in polar lake sediments. The method, involving both instrumental and experimental stages, successfully identified 26 com- pounds, including chlorobenzenes, DDX, lindanes, aldrin, atrazine, and newer syn- thetic molecules. The instrumental stage developed a new dMRM method using GC-MS/MS, while the experimental stage explored the optimal combination of sol- vents for extraction and the stationary phase of the SPE technique. The method’s validity was confirmed on a certified reference material and applied to 16 sediment samples from Arctic and Antarctic lakes. The findings were then discussed and correlated with existing literature data, contributing to the field of environmental analysis.